(untitled) (Bangladesh Armed Forces Medical Journal, 2024)
Background: Pneumonia is one of the leading causes of mortality among under-five children contributing to 15% of deaths all over the world. More than 95% of all new cases of pneumonia in children less than 5 years occur in developing countries. The aim of this study is to evaluate the socio-demographic characteristics, clinical profile, laboratory parameters and management of hospitalized children presenting with pneumonia. Methods: A descriptive cross-sectional study was conducted among 178 children aged between 02-59 months who were admitted into Paediatrics ward of Combined Military Hospital (CMH), Jashore during the period of July 2020 to December 2021were evaluated. Data were collected by a trained physician from history, clinical examinations, laboratory findings and chest x-ray immediately after admission using a structured questionnaire with purposive sampling technique. All x-ray films were evaluated by radiologist and paediatrician independently. Results: A total of 178 cases suffering from pneumonia were studied. Among them majority (87.08%) of children were below 36 months of age with the highest frequency of pneumonia was seen bellow 12 months (42.70%) age group. 112(62.92%) patients were male and 66(37.08%) patients were female with male-female ratio 1.7:1. Most of the patients were of normal birth weight (81.46%), fully immunized (84.27%), better maternal education, from nuclear family (81.46%) and were exclusive breast feed (70.22%). Fever, cough, breathing difficulty, tachypnoea and crackles were present nearly all patients with pneumonia. Chest x-ray suggestive of bronchopneumonia in most of the cases (91.01%). All patients received antibiotics, duration of hospital stay ranged from 03 to 14 days, mean stay was about 05 days. Nearly all the patients (97.52%) were recovered and discharged with advice. Conclusion: Most of the patients with pneumonia were below 36 months of age with male predominance. Fever, cough, fast or difficult breathing were as a feature of pneumonia. Prompt administration of antibiotics to children with pneumonia significantly reduces the morbidity and mortality. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 31-37